Techniques to control the anesthetic depth levels - Antonio Salgado Castillo; Arquímedes Montoya Pedrón (Centro Provincial de Información de Ciencias Médicas, 2016)
Essential aspects of the classification process of anesthetic depth levels are presented by means of electroencefalographic signs. The abovementioned process is supported from an exhaustive study that allowed to specify its main aspects. Finally, a characterization of its current state is carried out, taking into account the main indexes of anesthetic depth and types of marketed displays.